A mixed methods needs assessment and gap analysis for establishment of a cancer research training program in East Africa. (2021) - Nyagabona, Sarah K; Mushi, Beatrice P; Selekwa, Musiba; Philipo, Godfrey S; Haddadi, Sumaiya; Kadhim, Emilie F; Breithaupt, Lindsay; Maongezi, Sarah; Mwaiselage, Julius; Balandya, Emmanuel; Leyna, Germana H; Loon, Katherine Van; et al.
No abstract available